2022
DOI: 10.3390/biology11081179
|View full text |Cite
|
Sign up to set email alerts
|

Too Close for Comfort? Isotopic Niche Segregation in New Zealand’s Odontocetes

Abstract: Species occurring in sympatry and relying on similar and limited resources may partition resource use to avoid overlap and interspecific competition. Aotearoa, New Zealand hosts an extraordinarily rich marine megafauna, including 50% of the world’s cetacean species. In this study, we used carbon and nitrogen stable isotopes as ecological tracers to investigate isotopic niche overlap between 21 odontocete (toothed whale) species inhabiting neritic, mesopelagic, and bathypelagic waters. Results showed a clear ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…There is disagreement within published literature regarding the suitability of lipid correction equations being extrapolated to different species for isotopic studies [ 72 ]. Therefore, lipids were extracted from a sub-set of ten G. m. edwardii skin samples ( Supplementary Material Table S2 ) to check the validity of using published lipid correction equations [ 69 , 73 , 74 , 75 ]. Samples were selected from one location only (FWS) based on, (1) extreme carbon and nitrogen isotope values in comparison to the rest of the dataset and, (2) a wide range of C:N mass ratios.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is disagreement within published literature regarding the suitability of lipid correction equations being extrapolated to different species for isotopic studies [ 72 ]. Therefore, lipids were extracted from a sub-set of ten G. m. edwardii skin samples ( Supplementary Material Table S2 ) to check the validity of using published lipid correction equations [ 69 , 73 , 74 , 75 ]. Samples were selected from one location only (FWS) based on, (1) extreme carbon and nitrogen isotope values in comparison to the rest of the dataset and, (2) a wide range of C:N mass ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Selected samples had C:N mass ratios ranging from 3.27–4.48 and C:N atomic ratios ranging from 3.81–5.23. The lipid correction equation, which was based on a bootstrapping approach using 74 samples of odontocetes, including G. m. edwardii from Peters et al [ 75 ], was found to be the best fit for the data. The lipid correction equation: δ 13 C corrected = 0.5301486 × δ 13 C − 7.322335 was applied to δ 13 C values for samples with a C:N mass ratio over 3.5.…”
Section: Methodsmentioning
confidence: 99%
“…Although rarely observed at sea, most beaked whale species are known to be relatively slow swimmers but very deep divers, with many feeding entirely on squid. Peters et al, (2022) suggested that foraging in extreme depths might put constraints on beaked whale morphology and may explain the chunky body shape. Many of the 16 beaked whales overlap in range and can effectively partition resources (Riccialdelli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many tropical seabird species rely on similar prey items, use other birds as information cues to detect prey, and forage in mixed‐species flocks (Ashmole, 1971 ; Ballance et al., 1997 ; Spear et al., 2007 ; Thiebault et al., 2014 ; Veit & Harrison, 2017 ), leading to questions about the degree to which tropical seabird species are able to coexist and practice niche partitioning. Little evidence for trophic segregation has been found for some species of fish (Teffer et al., 2015 ), sharks (Lear et al., 2021 ), cetaceans (Peters et al., 2022 ), and seabirds (Forero et al., 2004 ; Petalas et al., 2024 ; Weimerskirch et al., 2009 ), and this was attributed to food being sufficiently abundant to allow species to coexist, at least during specific periods of the year.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen isotopes (δ 15 N) increase predictably from prey to predator and are a useful proxy for the trophic position of the organism (DeNiro & Epstein, 1981 ; Hobson & Clark, 1992 ), while carbon isotopes (δ 13 C) increase predictably from inshore to offshore food webs (Cherel & Hobson, 2007 ). The isotopic niche and its dimensions have thus been used to study the trophic ecology and niches of several marine predators including fish (Kojadinovic et al., 2008 ; Teffer et al., 2015 ), sharks (Lear et al., 2021 ), cetaceans (Peters et al., 2022 ), and many species of seabirds (Kojadinovic et al., 2008 ; Navarro et al., 2015 ; Robertson et al., 2014 ; Shoji et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%